Pengamalan Beragama Anak Putus Sekolah Suku Terasing Daerah Tertinggal Di Desa Paramasan Bawah Kabupaten Banjar - Yusuf, Muhammad (IAIN Antasari Banjarmasin, 2015)
This study is aimed at finding out the religious practices and their affecting factorson school dropouts of remote tribes in Paramasan Bawah Village, Banjar Regency.The study is a field research with qualitative descriptive analysis. The result ofthe study has shown that some religious practices performed by the dropouts inthe local area includes the five daily prayers, Al-quran recitation, social gathering(arisan) and yasinan, and recitation of Islamic study group (pengajian majelis taâlim).Â However, those religious practices have not been performed optimally. Several factorsÂ affecting the practices are the village surrounding environment, family, and friends